2005
DOI: 10.1002/adem.200500071
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Stress Corrosion Cracking (SCC) of Magnesium Alloys

Abstract: This review aims to provide a foundation for the safe and effective use of magnesium (Mg) alloys, including practical guidelines for the service use of Mg alloys in the atmosphere and/or in contact with aqueous solutions. This is to provide support for the rapidly increasing use of Mg in industrial applications, particularly in the automobile industry. These guidelines should be firmly based on a critical analysis of our knowledge of SCC based on (1) service experience, (2) laboratory testing and (3) understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
303
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(333 citation statements)
references
References 76 publications
2
303
1
4
Order By: Relevance
“…The selective dissolution of magnesium in magnesium alloys is associated with stress corrosion cracking (SCC). 8 An evaluation of the sensitivity of zinc-silver alloys to SCC would hence also be of interest when further evaluating this new class of biodegradable alloys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective dissolution of magnesium in magnesium alloys is associated with stress corrosion cracking (SCC). 8 An evaluation of the sensitivity of zinc-silver alloys to SCC would hence also be of interest when further evaluating this new class of biodegradable alloys.…”
Section: Discussionmentioning
confidence: 99%
“…7 Hydrogen may also be absorbed by the remaining magnesium implant, which can result in hydrogen embrittlement and premature failure of loadbearing implants. 8 Iron, on the other hand, degrades too slowly for many applications and produces voluminous corrosion products, causing an increase in the volume of the implant. 9,10 Zinc (Zn) was recently suggested as an alternative degradable metal or alloy base.…”
Section: Introductionmentioning
confidence: 99%
“…All Al-containing magnesium alloys have been confirmed to be susceptible to SCC in distilled water [1]. Generally, the SCC susceptibility of Mg alloys tends to increase with the growing percentage of Al content [11], and a previous study even showed the SCC susceptibility achieved maximize with about 6% Al content [12].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys are very attractive light materials, due to a high strength to weight ratio, being pollution-free, non-toxic, and exhibiting easy recovery [1,2], etc. The applications of magnesium alloys in electronics, automobiles, aerospace and the biomedical field are rapidly increasing, but their high chemical reactivity and poor corrosion resistance still severely limit their wider application [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation